2016
DOI: 10.1073/pnas.1524774113
|View full text |Cite
|
Sign up to set email alerts
|

Photodegradation of retinal bisretinoids in mouse models and implications for macular degeneration

Abstract: Adducts of retinaldehyde (bisretinoids) form nonenzymatically in photoreceptor cells and accumulate in retinal pigment epithelial (RPE) cells as lipofuscin; these fluorophores are implicated in the pathogenesis of inherited and age-related macular degeneration (AMD). Here we demonstrate that bisretinoid photodegradation is ongoing in the eye. High-performance liquid chromatography (HPLC) analysis of eyes of dark-reared and cyclic light-reared wild-type mice, together with comparisons of pigmented versus albino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
111
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 93 publications
(129 citation statements)
references
References 62 publications
2
111
0
Order By: Relevance
“…This molecule has been described to be involved in the pathogenesis of age-related macular degeneration (AMD) [52,53] and Stargardt disease [54]. A2E is known to be able to produce cytotoxicity by destabilizing membranes, generating reactive oxygen species and producing photo-oxidation [55][56][57][58].…”
Section: Future Directionsmentioning
confidence: 99%
“…This molecule has been described to be involved in the pathogenesis of age-related macular degeneration (AMD) [52,53] and Stargardt disease [54]. A2E is known to be able to produce cytotoxicity by destabilizing membranes, generating reactive oxygen species and producing photo-oxidation [55][56][57][58].…”
Section: Future Directionsmentioning
confidence: 99%
“…More recently Ref. [56] showed that RPE-lipofuscin photodegradation takes place in mouse eyes under standard ambient illumination. Speciically, they found that WT and ABCA4 −/− mice reared in constant darkness contained 45 and 62% more LBs in the RPE than their respective 12-h cyclic light-reared controls.…”
Section: Phototoxicitymentioning
confidence: 99%
“…The primary amine of PE in photoreceptor cell outer segments is notable for being subject to the reactivity of vitamin A aldehyde (all-trans-retinal or 11-cis-retinal) (6) that is essential to photon absorption by photoreceptor cells . The resulting Schiff base adduct, N-retinylidene-PE (NRPE) (7) serves to chaperone reactive retinaldehyde until it is reduced to all-trans-retinol by NADPH-dependent retinol 4 reaction is a [1,6]-proton tautomerization generating a phosphatidylethanolamine-retinyl enamine, which reacts with the second retinaldehyde.…”
Section: Introductionmentioning
confidence: 99%
“…The resulting Schiff base adduct, N-retinylidene-PE (NRPE) (7) serves to chaperone reactive retinaldehyde until it is reduced to all-trans-retinol by NADPH-dependent retinol 4 reaction is a [1,6]-proton tautomerization generating a phosphatidylethanolamine-retinyl enamine, which reacts with the second retinaldehyde. After aza-6π-electrocyclization and auto-oxidation of the dihydroopyridinium intermediate (dihydro-A2PE) (12) the fluorescent phosphatidyl-pyridinium bisretinoid A2PE is formed.…”
Section: Introductionmentioning
confidence: 99%